Kidnapping and violence: new research and clinical perspectives - Morewitz, Stephen John (Springer, 2019)
Partner Abduction and Hostage-Taking -- Bride Abduction -- Family Abduction in the United States -- International Family Abduction -- Nofamily Juvenile Abduction -- Responses to Abducted Children -- Infant Abduction -- Kidnapping by Cesarean Section and State-Sponsored Abduction of Newborns -- Human Trafficking -- Ransom Kidnapping -- Kidnapping: Carjacking and Related Crimes -- Aircraft Hijacking -- Maritime Piracy and Kidnapping -- Kidnapping Hoaxes